2015
DOI: 10.1108/ijppm-06-2013-0119
|View full text |Cite
|
Sign up to set email alerts
|

Involvement and productivity of research and development workers

Abstract: Purpose – The effect of global integration of businesses and interchange of ideas and technology through internet has many facets. Increase in economic recessions and decrease in research funding has forced both private and public sector research organizations to introduce measures of self-sustainability. Enhancing research and development (R&D) productivity of researchers can be one of those measures. The purpose of this paper is to attempt toward identifying and analyzing those factors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Barney et al (2022) examining data collected from 324 management faculties at public universities in the USA disclose that there are no single job resources that predict research productivity. Kumari et al (2015) based on the theoretical background and nature of data availability found that the research and development productivity of the researchers has a positive correlation with the extent of their involvement in the R&D projects. Gaus et al (2021) in a study of qualitative approach by interviewing 40 academics in 4 public universities in Indonesia demonstrated that individual factors contributed to the productivity of academics in science instead of institutional factors as compared to academics of social science.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Barney et al (2022) examining data collected from 324 management faculties at public universities in the USA disclose that there are no single job resources that predict research productivity. Kumari et al (2015) based on the theoretical background and nature of data availability found that the research and development productivity of the researchers has a positive correlation with the extent of their involvement in the R&D projects. Gaus et al (2021) in a study of qualitative approach by interviewing 40 academics in 4 public universities in Indonesia demonstrated that individual factors contributed to the productivity of academics in science instead of institutional factors as compared to academics of social science.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Research is a team work and follows a systematic process which tends to be impacted by more than one individual, organizational and environmental factors viz. attitude & priority of the team members, organizational support and government policies (Babu and Singh, 1998;Landry et al, 1996;Bonaccorsi and Daraio, 2003;Stack, 2004;Turner and Mairesseb, 2005;Ohly et al, 2006;Anderson et al, 2007;Jacso, 2008;Post et al, 2009;Kelchtermans and Veugelers, 2011;Obembe, 2012;Prathap, 2013;Ryu and Choi, 2016, Kumari et al, 2015, 2018and 2020. Hence, in this context Hypothesis 2 has been defined.…”
Section: Hypothesismentioning
confidence: 99%
“…The author also explained the role of flexibility in working characteristics and earning opportunities, encourage the elderly workforce to make use of their experience and increase the duration of their career. Kumari et al (2015Kumari et al ( , 2018 have considered "Man-days Involvement" as a significant determinant of productivity for researchers of CSIR -India laboratories. According to the authors, a large extent of man-days (working days) involvement in "grant-in-aid" R&D projects can provide opportunities and resources to focus on generating a greater number of publications to the researchers.…”
Section: Determinants Of Randd Productivitymentioning
confidence: 99%
See 2 more Smart Citations